2022
DOI: 10.1039/d2mh00593j
|View full text |Cite
|
Sign up to set email alerts
|

Reusable radiochromic hackmanite with gamma exposure memory

Abstract: Hackmanites are reusable and non-toxic materials for radiochromic films. They show a unique “gamma memory” function where the width of the reflectance spectrum changes permanently, but the ability to change color reversibly remains fully functional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…This reversibility makes Th-pba-0D reusable for radiation detection, an applaudable feature that allows for developing cost-effective radiation sensors. [23] Juxtaposed to Th-pba-0D, Th-pba-2D is neither radiochromic nor photochromic, giving credence to the essential role of structure in determining the photophysics of materials. [24] The UV-vis absorption spectrum of unirradiated Th-pba-2D is similar to that of Th-pba-0D owning to their identical components as shown in Figure 3c.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reversibility makes Th-pba-0D reusable for radiation detection, an applaudable feature that allows for developing cost-effective radiation sensors. [23] Juxtaposed to Th-pba-0D, Th-pba-2D is neither radiochromic nor photochromic, giving credence to the essential role of structure in determining the photophysics of materials. [24] The UV-vis absorption spectrum of unirradiated Th-pba-2D is similar to that of Th-pba-0D owning to their identical components as shown in Figure 3c.…”
Section: Resultsmentioning
confidence: 99%
“…This reversibility makes Th‐pba‐0D reusable for radiation detection, an applaudable feature that allows for developing cost‐effective radiation sensors. [ 23 ]…”
Section: Resultsmentioning
confidence: 99%
“…As a matter of fact, an artificial modification of the tetrahedron structure was observed after irradiating a sodalite material with X-rays or g-rays. 4,39 Indeed, subsequent to the irradiation, X-ray diffraction measurements show the formation of NaCl in its own phase along with the material still possessing its sodalite structure made of b-cages. Besides, a modification of the material's F-center absorption is reported.…”
Section: àmentioning
confidence: 99%
“…Recent developments into their synthetic analogues, some of which also display attractive luminescence properties, have shown that they have potential to be developed for a huge range of possible applications. The unique combination of white-to-pink reversible photochromism sensitive to UV 19 , X-rays 20 and gamma radiation 21 , along with orange and blue-white photoluminescence as well as persistent luminescence, means these materials could find future use as safety lighting 22 , X-ray imaging solutions 20 , radiation detectors 20,21 , dosimeters 20,21,23 , in diagnostics 22 and in energy storage 22 , to name just a few. These materials are also highly robust and do not require any expensive, toxic or endangered elements.…”
Section: Introductionmentioning
confidence: 99%